Equitable Allocations in Experimental Bargaining Games: Inequality A version versus Efficiency - Dorothea K. Herreiner; Clemens Puppe (University of Bonn, Bonn Graduate School of Economics (BGSE), 2004)
In this paper, we report on a series of free-form bargaining experiments in which two players have to distribute four indivisible goods among themselves. In one treatment the monetary payoffs associated with each bundle of goods are common knowledge; in a second treatment only the ordinal ranking of the bundles is given. We find that in both cases, the following qualitative rule yields a good explanation of individual behavior: First determine the most equal distribution, then find a Pareto improvement provided that this does not create “too much” inequality. In the ordinal treatment, individuals apparently use the ranks in the respective preference orderings over bundles as a substitute for the unknown monetary value. Interestingly, we find much less Pareto-damaging behavior due to inequality aversion in the ordinal treatment.
Keywords: 330